2020
DOI: 10.1007/s11126-020-09759-w
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Basic Hope and Depression: Forgiveness as a Mediator

Abstract: Although hope and forgiveness have been both negatively correlated with depression, actual relationships between all three variables have never been investigated. The aim of the study was to examine a theoretical model in which forgiveness mediates the relationship between basic hope and depressive symptoms. The sample was composed of 77 psychotherapy outpatients. Polish adaptations of the Basic Hope Inventory, the Beck Depression Inventory, and the Heartland Forgiveness Scale were used. Negative and positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 50 publications
3
31
0
4
Order By: Relevance
“…The hope aroused by gratitude can make the medical staff who affected by the pandemic distract their attention from the clues such as negative news reports related to the pandemic, and urge individuals to pay attention to more positive information. In addition, hope can make the medical staff cope with a series of frustration experiences better during the pandemic, help them discover the positive connotation behind the disaster, and promote them to fully explore their own potential to deal with difficulties, and finally play a role in reducing depression ( Snyder, 2002 ; Hassija et al, 2012 ; Kaleta and Justyna, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hope aroused by gratitude can make the medical staff who affected by the pandemic distract their attention from the clues such as negative news reports related to the pandemic, and urge individuals to pay attention to more positive information. In addition, hope can make the medical staff cope with a series of frustration experiences better during the pandemic, help them discover the positive connotation behind the disaster, and promote them to fully explore their own potential to deal with difficulties, and finally play a role in reducing depression ( Snyder, 2002 ; Hassija et al, 2012 ; Kaleta and Justyna, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“… Witvliet et al (2019) found that by letting the individuals recall people or things that deserve gratitude in the past, their hope for the future could be effectively improved. Increasing individuals’ hope can help them to distract their attention from negative events, and promote individuals to adopt more adaptive strategies to deal with negative events, thus alleviating depression symptoms ( Snyder, 2002 ; Kaleta and Justyna, 2020 ). An empirical study on post-traumatic groups also found that the higher the level of hope, the lower the level of depression ( Hassija et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers Kaleta and Mroz (2020) believe that forgiveness may be a mechanism by which hope reduces the likelihood of depression. Forgiveness can help reduce anger, depression, and anxiety and increase empathy, hope, and life satisfaction (Asici, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…basic hope. Research on basic hope is limited (Kaleta and Mróz, 2020;Wojciechowska, 2011). It has not been previously studied in postpartum mothers, including those who gave birth prematurely.…”
Section: Methodsmentioning
confidence: 99%